The Impact of Supervision on Bank Performance - HIRTLE, BEVERLY; KOVNER, ANNA; PLOSSER, MATTHEW (Journal of Finance, 2020)
ABSTRACT We explore the impact of supervision on the riskiness, profitability, and growth of U.S. banks. Using data on supervisors' time use, we demonstrate that the top‐ranked banks by size within a supervisory district receive more attention from supervisors, even after controlling for size, complexity, risk, and other characteristics. Using a matched sample approach, we find that these top‐ranked banks that receive more supervisory attention hold less risky loan portfolios, are less volatile, and are less sensitive to industry downturns, but do not have lower growth or profitability. Our results underscore the distinct role of supervision in mitigating banking sector risk.